Preparing for the next respiratory pathogen pandemic: using tabletop simulation exercises to strengthen national planning in Cook Islands, Costa Rica, Lebanon and Mongolia - Chugh, Hitesh; Akande, Oluwatosin Wuraola; Arroba Tijerino, Roberto; Assi, Moubadda; Bates, Metua; Berry, Atika; Brenes, Hebleen; Buyanbaatar, Dulamragchaa; Chuluunbat, Urtnasan; Danzan, Gerelmaa; Darmaa, Oyungerel; Garcia, Ingrid; et al. (Frontiers in Public Health, 2024)
The Preparedness and Resilience for Emerging Threats (PRET) initiative takes an innovative mode-of-transmission approach to pandemic planning by advocating for integrated preparedness and response systems and capacities for groups of pathogens with common transmission pathways. The World Health Organization (WHO) launched this initiative in 2023 with the publication of PRET Module 1 addressing respiratory pathogens. Exercise PanPRET-1 is a customizable tabletop simulation exercise (TTX) package developed to complement PRET Module 1. The exercise scenario focuses on strengthening capacities for multisectoral coordination, risk communication and community engagement, and the triggers for operational decision-making. This article reports on the experiences of the first four countries to implement Exercise PanPRET-1: Cook Islands, Costa Rica, Lebanon and Mongolia. Exercise outcomes demonstrated that PanPRET-1 can be an effective tool for testing pandemic plans in a multisectoral forum and identifying opportunities to improve preparedness and response in key domains. In quantitative evaluations in Cook Islands, Costa Rica and Mongolia, high proportions of exercise participants indicated that multiple aspects of the exercise were well-designed and were beneficial for improving health emergency preparedness. Exercise participants in Lebanon provided qualitative feedback indicating that they found the exercise to be beneficial. Conducting a TTX and monitoring the implementation of action plans based on exercise findings facilitates a country-owned whole-of-society vision for pandemic planning. Countries are encouraged to incorporate TTX such as Exercise PanPRET-1 into a continuous cycle of activity to improve pandemic preparedness.